Peran Kepolisian Lalu Lintas Dalam Pencegahan Pelanggaran Lalu Lintas Oleh Anak Sebagai Pengendara Sepeda Motor Di Kota Padang (Studi Kasus Polresta Padang) - Sufiyani; Elwidarifa Marwenny (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
In Padang City, there are many traffic violations committed by children under the age of 17 who use motorized vehicles. From the data in 2022, 3098 cases of traffic violations occurred due to children, even though it is regulated in Law Number 22 of 2009 concerning Road Traffic and Transportation which says that to drive a motorcycle you must have a driver's license and be 17 years old. Based on this, this research aims to find out: a) What are the factors that cause traffic violations by children: b) How is the role of the Padang City Police in preventing traffic violations against minors: c) What are the obstacles faced by the Padang Police in preventing traffic violations by minors. This research was conducted in the Padang City area. To answer the above questions, the research method used is a qualitative method with a Juridical Sosilogis approach (socio legal research), namely an approach to the problem by looking at legal norms and occurring in the field found, using primary data as the main data, namely by conducting interviews and secondary data in the form of literature studies and conclusions obtained, namely: a) The factors that cause children to commit violations are in the form of social factors, educational factors and family or parental factors, because their souls are still unstable and carelessness in driving, lack of knowledge about traffic signs: b) The role of the traffic police here is to prevent in two ways, namely preventive and repressive, namely by conducting counseling to schools to introduce traffic ethics early on and by reprimanding children or adolescents who violate. Legal regulation of traffic violations against motorists who commit violations, the traffic police will take action or impose sanctions on violators in accordance with the Articles violated in Law Number 22 of 2009: c) The obstacles faced by the police in this study are in the form of internal and external factors, internal factors originating from within the police themselves and external factors originating from outside, namely from the community itself.